Early mobilization and quality of life after stroke: Findings from AVERT. (13th August 2019) - Cumming, Toby B.; Churilov, Leonid; Collier, Janice; Donnan, Geoffrey; Ellery, Fiona; Dewey, Helen; Langhorne, Peter; Lindley, Richard I.; Moodie, Marj; Thrift, Amanda G.; Bernhardt, Julie
Abstract : Objective: To determine whether early and more frequent mobilization after stroke affects health-related quality of life. Methods: A Very Early Rehabilitation Trial (AVERT) was an international, multicenter (56 sites), phase 3 randomized controlled trial, spanning 2006–2015. People were included if they were aged ≥18 years, presented within 24 hours of a first or recurrent stroke (ischemic or hemorrhagic), and satisfied preordained physiologic criteria. Participants were randomized to usual care alone or very early and more frequent mobilization in addition to usual care. Quality of life at 12 months was a prespecified secondary outcome, evaluated using the Assessment of Quality of Life 4D (AQoL-4D). This utility-weighted scale has scores ranging from −0.04 (worse than death) to 1 (perfect health). Participants who died were assigned an AQoL-4D score of 0. Results: No significant difference in quality of life at 12 months between intervention (median 0.47, interquartile range [IQR] 0.07–0.81) and usual care (median 0.49, IQR 0.08–0.81) groups was identified ( p = 0.86), nor were there any group differences across the 4 AQoL-4D domains. The same lack of group difference in quality of life was observed at 3 months. When cohort data were analyzed (both groups together), quality of life was strongly associated with acute length of stay, independence in activities of daily living, cognitive function, depressive symptoms, and anxiety symptoms (all p < 0.001). Quality of life in AVERT participants was substantially lower than population norms, and the gap increased with age. Conclusions: Earlier and more frequent mobilization after stroke did not influence quality of life. Clinical trial registration: anzctr.org.au ; ACTRN12606000185561 Classification of evidence: This study provides Class II evidence that for people with stroke, earlier and more frequent mobilization did not influence quality of life over the subsequent year.